Pengaruh Pendidikan Sejak Anak Usia Dini Bagi Orang Tua di Desa Sigala-Gala - Mahmudin Hasibuan; Nur Jamilah; Roimah Subuh; Ningsih Ayuni; Miftahul Jannah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of early childhood education on parents in Sigala-gala Village. Early childhood education plays an important role not only for child development but also in shaping parents' awareness of parenting and involvement in children's education. This research used a descriptive qualitative method with the research subjects consisting of four parents, the village head, the customary leader, and the early childhood education teacher. Data were collected through observation, interviews, and documentation, then analyzed by data reduction, data presentation, and conclusion drawing and tested for validity using credibility, transferability, dependability, and confirmability. The results show that the presence of PAUD in Sigala-gala Village has a positive impact on parents, namely increased attention in supporting children's learning process, understanding the importance of early stimulation, and awareness to cooperate with educational institutions.